Optimalisasi Potensi Wisata Melalui Edusport Tourism di Telaga Ngrejek Gunung Kidul untuk Mewujudkan Desa Wisata - Nurhadi Santoso; Ratna Kumala Setyaningrum; Masri Masri; Agus Wiyanto (Universitas PGRI Semarang, 2023)
The purpose of this community service is to raise awareness among the community regarding the existing potential of Ngrejek Lake and to optimize the tourism management by the youth organization (karang taruna) and the community empowerment group (Pokdasawisma), through providing assistance in terms of Edu-Sport Tourism and promoting the